2003
DOI: 10.1016/s1476-5586(03)80018-0
|View full text |Cite
|
Sign up to set email alerts
|

WISP-2 Gene in Human Breast Cancer: Estrogen and Progesterone Inducible Expression and Regulation of Tumor Cell Proliferation

Abstract: WISP-2 mRNA and protein was overexpressed in preneoplastic and cancerous cells of human breast. Statistical analyses show a significant association between WISP-2 expression and estrogen receptor (ER) positivity. In normal breast, the expression was virtually undetected. The studies showed that WISP-2 is an estrogen-induced early response gene in MCF-7 cells and the expression was continuously increased to reach a maximum level at 24 h. The estrogen effect was inhibited by a pure antiestrogen (ICI 182,780). Hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
110
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(118 citation statements)
references
References 33 publications
7
110
1
Order By: Relevance
“…Importantly, they were able to extend this observation to the in vivo setting by showing a strong correlation between expression of CCN5 protein and estrogen receptor alpha (ER-α) positivity in human breast cancer samples (Banerjee et al 2003). Progesterone was also shown to induce CCN5 protein in ER-positive human breast cancer cells.…”
Section: Estrogen Signalingmentioning
confidence: 86%
See 2 more Smart Citations
“…Importantly, they were able to extend this observation to the in vivo setting by showing a strong correlation between expression of CCN5 protein and estrogen receptor alpha (ER-α) positivity in human breast cancer samples (Banerjee et al 2003). Progesterone was also shown to induce CCN5 protein in ER-positive human breast cancer cells.…”
Section: Estrogen Signalingmentioning
confidence: 86%
“…Addition of 17β-estradiol to MCF-7 cells in culture increases expression of CCN5 mRNA and protein in a dose-dependent manner (Banerjee et al 2003;Inadera et al 2002). CCN5 protein levels in MCF-7 cells increase over 24 h and can reach maximum levels by 72 h (Banerjee et al 2003;Inadera et al 2002).…”
Section: Estrogen Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…CCN5 has also been described in human fetal bone (Kumar et al 1999); human pancreas (Dhar et al 2007); and breast ductal and lobular epithelium (Banerjee et al 2003). CCN5 protein and mRNA has also been detected in numerous cultured cells and tissue specimens using Western and Northern blots, respectively (summarized in Gray and Castellot 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies from our laboratory and others have suggested that WISP-2/CCN5 has a particular relevance to human breast disease (1,7,8). This is because WISP-2/CCN5 mRNA and protein levels were elevated in different human breast tumor-derived cell lines as well as in breast tumor samples while being barely detectable, or undetectable, in normal breast epithelial cells (7)(8)(9). Additionally, abnormal expression of the WISP-2/CCN5 gene was significantly higher in noninvasive carcinoma cells compared with invasive carcinoma cells.…”
Section: Introductionmentioning
confidence: 99%